IDENTIFIKASI KANDUNGAN SENYAWA FITOKIMIA MINYAK BIJI MIMBA (Azadirachta Indica, A. Juss) - Dyah Palupi; Endang Kusdiyantini; Rully Rahadian; A Heru Prianto (Jurnal Akademika Biologi, 2016)
Neem seeds oil (Azadirachta indica, A. Juss) have phytochemical compounds which act as antifeedant, repellent, antibacterial, and antifungal. The neem seeds oil were important identified their phytochemical compounds. Identifications were done with screening phytochemical and infrared spectrophotometer. Neem seed oils were obatained with pressing method. The group of compounds tested were alkaloid, flavonoid, triterpenoid, steroid, saponin and tannin. The results of phytochemical showed that neem seeds oil consist of alkaloid, flavonoid, triterpenoid, steroid, saponin and tannin. This results were strengthned with spectrum in infrared spectrophotometer that showed the functional groups of each those compounds. Keywords: neem seeds oil, phytochemical compounds, pressing method, functional groups